1984
DOI: 10.1111/j.1365-2125.1984.tb05022.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and renal effects of nicardipine.

Abstract: Both the acute blood pressure lowering and renal effects of the calcium antagonist nicardipine and those after 1 week's treatment were investigated in 10 normotensive volunteers and in 10 patients with mild to moderate essential hypertension. 2 After 1 week of placebo, nicardipine was administered orally for 1 week (20 mg three times daily), Investigations, done on the first and last day of nicardipine treatment were compared with those on the last day of placebo. 3 During water loading, nicardipine increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Other studies revealed that short-term treatment with diltiazem 62 or nifedipine 66 or administration of nicardipine 67 for 1 week produced a reduction of blood pressure in hypertensive subjects comparable to that induced by identical doses in normotensive subjects (see Table 3). However, the increases in RBF, 6667 GFR, 66 and U N , were greater in hypertensive than in normotensive subjects.…”
Section: Reported Effects Of Calcium Blockers On Renal Hemodynamicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies revealed that short-term treatment with diltiazem 62 or nifedipine 66 or administration of nicardipine 67 for 1 week produced a reduction of blood pressure in hypertensive subjects comparable to that induced by identical doses in normotensive subjects (see Table 3). However, the increases in RBF, 6667 GFR, 66 and U N , were greater in hypertensive than in normotensive subjects.…”
Section: Reported Effects Of Calcium Blockers On Renal Hemodynamicsmentioning
confidence: 95%
“…These findings could have important clinical implications. In fact, an exaggerated increase in intrarenal resistance found in approximate- 62 Leonetti et al 63 Leonetti et al 65 Yokoyama and Kaburagi 66 Van Schaik et al 67 Normotension Leonetti et al 63 Leonetti et aJ. H …”
Section: Reported Effects Of Calcium Blockers On Renal Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term administration of nifedipine to normotensive subjects or hypertensive patients produced a significant increase in plasma renin activity (Aoki et al, 1976;Pedersen et al, 1979;Hiramatsu et al, 1982;Kusano et al, 1982;Leonetti et al, 1982;Kiowski et al, 1983). Results for plasma RAS components were inconsistent after treatment with nitrendipine (Thananopavarn et al, 1984;Luft et al, 1985;Pedrinelli et al, 1986), nicardipine (van Schaik et al, 1984;Elliott et al, 1985), amlodipine (Krenek et al, 2004;Lamarre-Cliche et al, 2005), or verapamil (Muiesan et al, 1982;Guthrie et al, 1983;Frohlich, 1985). Some calcium blockers such as azelnidipine may suppress the RAS although its mechanism remains unclear (Oizumi et al, 1989).…”
Section: Calcium Blockersmentioning
confidence: 99%
“…More recently this diuretic and natriuretic capacity has been confirmed for a number of related calcium antagonists e.g. nifedipine (Ene et al, 1985), nitrendipine (Ene etal., 1985;Wallia etal., 1985), nicardipine (van Schaik et al, 1984), and felodipine (Sluiter et al, 1985). As reviewed elsewhere, several mechanisms could account for this natriuretic effect, and the tubular site of action is still debated (Zanchetti & Leonetti, 1985).…”
Section: Introductionmentioning
confidence: 99%